Influence of Interpersonal Communication Partner on Uptake of Voluntary Medical Male circumcision among Married Men in Kenya: An Evaluation Study of Information Source attributes - Emojong', Omukule (Advances in Social Sciences Research Journal, 2020)
Background Studies have shown that male circumcision offers partial “vaccine” against heterosexually acquired HIV as a result WHO recommended it as one of the strategies to fight the AIDS scourge. Married and older men have registered low uptake of the “cut” in the targeted communities in Kenya. Considerable evidence suggests that communication inequality and choice of interpersonal information source are determinants in adoption of healthy behaviours such as adoption of male circumcision. This study aimed to examine how interpersonal communication source attributes (trust, similarity and expertise) may influence uptake of male circumcision among married men in Busia County, Kenya. Methods Voluntary medical male circumcision (VMMC) programme targets males aged up to 49 years. This study targeted married men aged between 20 and 49 years. Measures included socio-demographic characteristics, sources of VMMC information, perception on interpersonal source attributes of trust, expertise, and similarity between source and recipient. Sources regarded as trusted and expert were also measured including similarity dimensions of ethnicity, gender, age and marital status. A total of 377 participants completed the self-administered questionnaires, giving a response rate of 100%. Descriptive statistics tables such as those showing frequencies, mean and standard deviation of constructs were used. Due to the nature of the data collected, the Pearson Product-Moment Correlation Coefficient was computed to measure the relationship between socio-demographic characteristics and interpersonal communication source attribute. Results The Pearson Correlation computed revealed there existed a significant positive correlation between age and source trustworthiness and negative correlation with expertise. Marriage duration had a significant positive correlation with trustworthiness of source attribute. Trusted source was a friend. A health care provider was regarded as an expert source while similarity between source and recipient dimensions of age and ethnicity were given more weight. Health worker was the most popular source of VMMC information. Conclusion This study has revealed fundamental insights and provided evidence that the quality of the message carrier and demographic characteristics are critical factors to consider in implementing VMMC programme especially targeting married and older men who register low uptake. VMMC programmes using interpersonal channels must put more premium on the choice of the messenger as trust and expertise of source including similarity between communication partners is vital in the success of such communication interventions involving adoption of a sensitive cultural and sexual issue especially targeting married men.